Knowledge and attitudes toward rational antibiotic use among non-health-related undergraduate students in Lampung, Indonesia: a cross-sectional study - Yasinda Oktariza; Uswatun Hasanah; Juwana Janu; Delladari Mayefis (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2025)
Background: Inappropriate antibiotic use drives antimicrobial resistance (AMR), a growing global health threat. Non-health-related undergraduate students represent a population with limited formal health education yet significant potential to influence community antibiotic use behaviors. Objective: This study assessed knowledge and attitudes toward rational antibiotic use among non-health-related undergraduate students at Institut Teknologi Sumatera (ITERA), Lampung, Indonesia, and examined the relationship between the two. Methods: A cross-sectional study was conducted among 288 non-health-related undergraduate students from three faculties at ITERA between July and September 2025. Data were collected using a validated, adapted questionnaire. Descriptive statistics, Kruskal-Wallis and one-way ANOVA tests, and Spearman's rank correlation were performed. Results: Mean knowledge and attitude scores were 59.98 (SD = 20.20) and 59.23 (SD = 20.82), respectively, both in the moderate category. Key misconceptions included beliefs that antibiotics treat viral infections (48.97%), reduce fever (45.52%), and can be purchased online without a prescription (62.76%). A moderate-to-strong positive correlation was identified between knowledge and attitude (rho = 0.650; 95% CI: 0.575 to 0.714; p < 0.001). Conclusion: Non-health-related undergraduate students at ITERA demonstrated moderate yet insufficient antibiotic knowledge and attitudes. University-level educational interventions are warranted to improve antibiotic literacy and support AMR containment efforts.